2015
DOI: 10.1096/fasebj.29.1_supplement.lb513
|View full text |Cite
|
Sign up to set email alerts
|

Integration of G Protein Alpha (Gα) Signaling by the Regulator of G Protein Signaling 14

Abstract: RGS14 contains distinct binding sites for both active (GTP bound) and inactive (GDP bound) forms of Gα proteins. The N‐terminal RGS domain binds active Gαi/o‐GTP, whereas the C‐terminal GPR motif binds inactive Gαi1/3‐GDP. The molecular basis for how RGS14 binds different activation states of Gα to integrate G protein signaling is unknown. Here we explored the effects of G protein binding on the GPR motif and the RGS domain, and examined whether RGS14 can functionally interact with two forms of Gα simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…RGS14 has a number of functional domains/motifs that are distinct from its RGS domain, so RGS14 actions on mGluR-LTD could be independent of its GAP activity. Consistent with this idea, RGS14 contains a GPR motif that is required for plasma membrane anchoring (Brown et al, 2015), and this motif was found to be essential for RGS14 regulation of synaptic plasticity in hippocampal neurons independent of the RGS domain function (Squires et al, 2021). Additionally, RGS14 binds active H-Ras to inhibit ERK signaling (Shu et al, 2010).…”
Section: Discussionmentioning
confidence: 67%
“…RGS14 has a number of functional domains/motifs that are distinct from its RGS domain, so RGS14 actions on mGluR-LTD could be independent of its GAP activity. Consistent with this idea, RGS14 contains a GPR motif that is required for plasma membrane anchoring (Brown et al, 2015), and this motif was found to be essential for RGS14 regulation of synaptic plasticity in hippocampal neurons independent of the RGS domain function (Squires et al, 2021). Additionally, RGS14 binds active H-Ras to inhibit ERK signaling (Shu et al, 2010).…”
Section: Discussionmentioning
confidence: 67%
“…The G protein regulatory (GPR)/GoLoco motif binds inactive Gαi1/3-GDP (Hollinger et al, 2001;Kimple et al, 2001;Mittal & Linder, 2004). Binding of RGS14 to inactive Gαi1-GDP or Gαi3-GDP serves to anchor RGS14 at the plasma membrane thereby allowing for the RGS domain to bind and GAP a second active Gαi/o (Figure 1) (Brown et al, 2015;Brown et al, 2016).…”
mentioning
confidence: 99%